2021
DOI: 10.3390/healthcare9020235
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Registered Dietitian Nutritionists on Adoption of Telehealth for Nutrition Care during the COVID-19 Pandemic

Abstract: Widespread transmission of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has resulted in a global coronavirus disease 2019 (COVID-19) pandemic that is straining medical resources worldwide. In the United States (US), hospitals and clinics are challenged to accommodate surging patient populations and care needs while preventing further infection spread. Under such conditions, meeting with patients via telehealth technology is a practical way to help maintain meaningful contact while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 24 publications
1
51
0
1
Order By: Relevance
“…The use of telehealth has significantly increased in the COVID-19 era, with significant benefits described in terms of improved access and efficiency of services [ 30 ]. Conducted prior to pandemic restrictions, this study demonstrated a very low use of telehealth, as well as community-based dietetics.…”
Section: Discussionmentioning
confidence: 99%
“…The use of telehealth has significantly increased in the COVID-19 era, with significant benefits described in terms of improved access and efficiency of services [ 30 ]. Conducted prior to pandemic restrictions, this study demonstrated a very low use of telehealth, as well as community-based dietetics.…”
Section: Discussionmentioning
confidence: 99%
“…Although online recruitment may have impacted sample size, the successful online administration of the questionnaire can be seen as a strength. The global pandemic has changed the way healthcare is delivered and it is anticipated that health education programs will increasingly be delivered through remote methods such as ehealth and telehealth [ 77 , 78 ]. This study has demonstrated that the Med-NKQ has good application in an online environment.…”
Section: Discussionmentioning
confidence: 99%
“…A 20-question survey emailed by the Academy of Nutrition and Dietetics (ADA) between 24 August and 11 September 2020 collected responses from 22 registered dietician nutritionists (RDNs) [138]. The responses showed that, prior to the pandemic, 15 hospitals had not provided nutritional care via telemedicine.…”
Section: During the Covid-19 Pandemicmentioning
confidence: 99%
“…The questionnaire revealed that mainly telephone calls were used during COVID-19, along with videoconferencing and remote patient monitoring. The RDNs reported that it was difficult to conduct nutritional focused physical exams (NFPEs); on the other hand, they could manage to have a longer assessment time and to look at the patient's home environment and nutrition habits [138].…”
Section: During the Covid-19 Pandemicmentioning
confidence: 99%